Semantic-Style Characteristics of Certain Color Defining Adjectives in The Modern Uzbek Language - Maftuna Gazieva; Oripova Sevara (Zien Journals, 2023)
This article presents opinions about the connotative meaning of adjectives denoting color. The article also provides information on the use of color adjectives and their analysis.
Keywords: adjective; connotative meaning; color adjectives